Biochemical basis of seed deterioration - an overview - ANIL DAHUJA,; SANGITA YADAV, (Seed Research, 2026)
Seeds die inevitably but unexpectedly during storage. Seed deterioration is loss of seed quality, viability and vigor due to effect of adverse environmental factors. It is a natural process and once seed deterioration has started, this catabolic process cannot be reversed. Biochemical processes of lipid peroxidation and associated free radical oxidative stress are one of the major causes of seed deterioration. Reactive oxygen species (ROS) are highly reactive, unstable and may react and damage nearby molecules. They may modify and inactivate proteins, lipids, DNA, RNA leading to inactivation of enzymes or decrease in proteins, disintegration of cell membranes, genetic damage and also induce cellular dysfunctions. In addition, loss of the glassy state and cellular repair mechanisms is also considered as driving force for seed deterioration. Thus, knowing and understanding the complexities of factors governing seed deterioration are therefore of major agronomical and economical importance.